The comparative performance in college mathematics of special science and general revised secondary curricula of MSU-IIT - Castardo-Padura, Digna Lumayag
This study compared the performance in college mathematics of the first two batches of graduates under the Special Science Curriculum (SSC) who graduated in 1982 and 1983 and those who graduated under the General Revised Secondary Curriculum (GRSC) of the Developmental High School, MSU—11igan Institute of technology during the same years.